Induction of sprouting on physicochemical profile and bioactive compounds in peach cultivars by foliar applications - Ferreira, Rafael Bibiano [UNESP]; Leonel, Sarita [UNESP]; Silva, Marcelo de Souza [UNESP]; Souza, Jackson Mirellys Azevêdo [UNESP]; Bolfarini, Ana Carolina [UNESP]; Modesto, Joyce Helena [UNESP]; Filho, Vitor Hugo Artigiani (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2019)
The induction of sprouting is a fundamental practice to grow temperate fruits in warmer regions, as the use of alternative products are necessary. This study aimed to verify the influence of foliar nitrogen fertilizer application to induce bud sprouting at different doses in three types of peach cultivars, regarding fruit quality, in Botucatu, state of Sao Paulo. This study occurred at the experimental orchard of Botucatu Agriculture School of Universidade Estadual Paulista (FCA/UNESP) in 2015 and 2016. Evaluations consisted of three cultivars Douradão, BRS Kampai and BRS Rubimel; and four doses of foliar nitrogen fertilizer (0; 1.25; 2.50 and 3.75%) with 4% calcium nitrate in all treatments. A randomized experimental design was conducted with 12 treatments, 4 replicates and 5 fruits per plot, that is, 240 evaluated fruits in each productive cycle. Fruits produced by cultivar BRS Rubimel showed the highest mean mass among the others, being greater than 100 g, regardless of applied dose. In this study, different doses influenced physical, physicochemical and biochemical attributes of fruits in all cultivars. However, both cultivars showed good quality standards in terms of size, high soluble solids content and low acidity, being recommended for direct consumption in Botucatu, state of Sao Paulo.
Perfil físico-químico y compuestos bioactivos de los frutos de cultivares de durazno, sometidos a la aplicación de inductores de brotación
Keywords: Calcium nitrate; Cultural practices; Erger; Nitrogen foliar fertilizer; Prunus persica L